Community Engagement in State Islamic Higher Education Institutions: A Paradigmatic Critique - Zuhri, H.; Yahya, Padli Pawaid; Abroto, Abroto (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Community engagement serves as a vital bridge between the academic sphere and social reality. The community is the ideal partner in applying, developing, testing, and evaluating theoretical-conceptual ideas. However, community engagement within State Islamic Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Negeri, PTKIN) appears to be limited to a service-oriented paradigm, predominantly focused on religious services. This study examines these patterns through a qualitative-descriptive approach involving documentary analysis from Universitas Islam Negeri (UIN) Sunan Kalijaga, UIN Alauddin Makassar, UIN Batusangkar, and the Indonesian Ministry of Religious Affairs. Employing textual interpretation, comparative analysis, and critical reflection, the research identifies an outdated paradigm in PTKIN's community engagement, one that fails to adapt to shifting societal realities. The evolving nature of society necessitates a corresponding shift in the conceptual and practical framework of community engagement. A paradigmatic transformation is essential if community engagement at PTKIN is to remain relevant and contributive both to the university and the broader society.